In Acute IgA Nephropathy, Proteinuria and Creatinine Are in the Spot, but Podocyturia Operates in Silence: Any Place for Amiloride? - H. Trimarchi; M. Paulero; R. Canzonieri; A. Schiel; A. Iotti; C. Costales-Collaguazo; A. Stern; M. Forrester; F. Lombi; V. Pomeranz; R. Iriarte; T. Rengel; et al. (Case Reports in Nephrology)
IgA nephropathy is the most frequent cause of primary glomerulonephritis, portends erratic patterns of clinical presentation, and lacks specific treatment. In general, it slowly progresses to end-stage renal disease. The clinical course and the response to therapy are usually assessed with proteinuria and serum creatinine. Validated biomarkers have not been identified yet. In this report, we present a case of acute renal injury with proteinuria and microscopic hematuria in a young male. A kidney biopsy disclosed IgA nephropathy. Podocyturia was significantly elevated compared to normal subjects. Proteinuria, renal function, and podocyturia improved promptly after steroids and these variables remained normal after one year of follow-up, when steroids had already been discontinued and patient continued on valsartan and amiloride. Our report demonstrates that podocyturia is critically elevated during an acute episode of IgA nephropathy, and its occurrence may explain the grim long-term prognosis of this entity. Whether podocyturia could be employed in IgA nephropathy as a trustable biomarker for treatment assessment or even for early diagnosis of IgA nephropathy relapses should be further investigated.